Deep Learning based Bangla Voice to Braille Character Conversion System - Iqbal, Syed Bayes; Rifat, Riazul Islam; Hussain, Md Akif; Biswas, Simon (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.